A Review of Indonesia’s Biodiversity as a Resource for Epigenetic Research: Opportunities and Future Directions - Anisa Fitri Rahayu (Postgraduate, University of Mataram, 2025)
Indonesia, a megadiverse nation, possesses extraordinary biological wealth, including a vast array of medicinal plants, diverse fauna, and unique microbial ecosystems. This rich biodiversity, however, faces severe threats from habitat loss and climate change, underscoring the urgent need for its documentation and scientific utilization, particularly in emerging fields such as epigenetics. Epigenetics, which involves heritable changes in gene expression without altering the DNA sequence, is fundamental to understanding biological processes and disease. While foundational epigenetic discoveries often originate from microorganisms, Indonesia's extensive microbial and plant diversity, including endemic species, remains largely unexplored regarding its epigenetic potential. This review highlights Indonesia’s biodiversity, including representative species, as a promising source of novel model organisms for epigenetic research and bioactive metabolites with significant medical potential, which may possess epigenetic-modulating properties as natural ‘epidrugs’ inspired by traditional Indonesian herbal medicine known as jamu. Bridging biodiversity research with molecular epigenetics offers a powerful framework for identifying new epigenetic mechanisms, regulators, and natural compounds, opening new frontiers in personalized medicine and disease prevention within Indonesia's unique biological and cultural landscape.